Misoprostol-Induced Modification of the Notch Signaling Pathway in the Human Cervix. (July 2019) - Avci, Sema; Simsek, Mehmet; Soylu, Hakan; Ustunel, Ismail
The complex and multifactorial mechanisms that initiate and sustain the early labor process in the human uterus and cervix are still not well defined. Cervical maturation or ripening is likely to play a key role in preparing for birth. Prostaglandins have many different functions, including the regulation of uterine contractility and structure during pregnancy. The prostaglandin E1 analogue misoprostol is frequently used as a uterotonic and cervical ripening agent. Notch is a transmembrane receptor family responsible for basic functions such as cell survival, cell–cell communication, and differentiation and decidualization in pregnancy. However, our understanding of the effect of Notch signaling on the cervical ripening process is limited. This study was conducted in 20 pregnant women aged at 12 to 20 weeks of gestation undergoing medical abortion for fetal or maternal indications. True-Cut needle biopsies were taken from the anterior cervix 4 hours after oral ingestion of 200-μg misoprostol or before the ingestion of misoprostol in the control group. Cervical expression of Notch receptors and ligands changed during the early phase of prostaglandin-induced preterm labor. Four hours after the administration of misoprostol, it was seen that N1 expression increased in muscle, while DLL1 and J2 expression increased in blood vessels, and N4 expression increased in macrophages. Knowing the mechanisms that initiate preterm birth is the most important step in planning the treatments and actions to prevent premature birth. As a signal that affects and perhaps directs preterm labor, Notch is prone to be an important actor in this process.